Unusual type of scleromyxedema with multiple subcutaneous nodules, IgM-λ paraproteinemia, and scleroderma-like microangiopathy. Issue 2 (June 2021) - Awaji, Kentaro; Asano, Yoshihide; Takaoka, Mariko; Oka, Tomonori; Miyake, Tomomi; Suga, Hiraku; Sato, Shinichi
Scleromyxedema is a mysterious cutaneous mucinosis of unknown etiology. Various types of scleromyxedema variant have been reported, which often give us a clue to understand the key aspects of this disease. Here, we describe a woman with highly unusual type of scleromyxedema. In addition to the rare manifestations of multiple subcutaneous nodules and IgM-λ paraproteinemia, our patient showed several characteristic symptoms of scleroderma such as shortened nails and fingertips, sclerodactyly, and bone resorption of fingertips and mandibles as a result of peripheral circulatory insufficiency, although this disease is known to be pathophysiologically different from scleroderma. A skin biopsy revealed cutaneous microvascular stenosis and occlusion due to intravascular mucin deposition and fibrotic changes, suggesting that scleromyxedema potentially develops peripheral circulatory disorders and other vascular involvement. The subcutaneous nodules were responsive to high-dose intravenous immunoglobulin. Scleromyxedema can represent a wide variety of systemic involvement, and therefore, we should pay attention to those symptoms as well as skin lesions.